Exploring barriers to the delivery of cervical cancer screening and early treatment services in Malawi: some views from service providers - Munthali AC; Ngwira BM; Taulo F (Patient Preference and Adherence, 2015)
Alister C Munthali,1 Bagrey M Ngwira,2 Frank Taulo3 1Centre for Social Research, University of Malawi, Zomba, Malawi; 2The Polytechnic, University of Malawi, Blantyre, Malawi; 3College of Medicine, University of Malawi, Blantyre, Malawi Background: Cervical cancer is the most common reproductive health cancer in Malawi. In most cases, women report to health facilities when the disease is in its advanced stage. In this study, we investigate service providers’ perceptions about barriers for women to access cervical cancer screening and early treatment services in Malawi.Methods: We conducted in-depth interviews with 13 district coordinators and 40 service providers of cervical cancer screening and early treatment services in 13 districts in Malawi. The study was conducted in 2012. The district coordinators helped the research team identify the health facilities which were providing cervical cancer screening and early treatment services.Results: Almost all informants reported that cervical cancer was a major public health problem in their districts and that prevention efforts for this disease were being implemented. They were aware of the test and treat approach using visual inspection with acetic acid (VIA). They, however, said that the delivery of cervical cancer screening and early treatment services was compromised because of factors such as gross shortage of staff, lack of equipment and supplies, the lack of supportive supervision, and the use of male service providers. Informants added that the lack of awareness about the disease among community members, long distances to health facilities, the lack of involvement of husbands, and prevailing misperceptions about the disease (eg, that it is caused by the exposure to the VIA process) affect the uptake of these services.Conclusion: While progress has been made in the provision of cervical cancer screening and early treatment services in Malawi, a number of factors affect service delivery and uptake. There is a need to continue creating awareness among community members including husbands and also addressing identified barriers such as shortage of staff and supplies in order to improve uptake of services. Keywords: cervical cancer screening, HPV, Malawi, VIA, early treatment programs